Penerapan Model Pembelajaran Tematik Untuk Meningkatkan Berfikir Kreatif Siswa - Yuyun Yunita (MKKS SMA, MKKS SMP se-Kota Metro, Persatuan Sarjana Pendidikan Islam Wilayah Provinsi Lampung, dan CV.IQRO Penerbitan, 2018)
Thematic presents learning that emphasizes student learning activities that develop students' ability to ask questions, express opinions, and cooperate in study groups. The application of thematic learning models is expected to increase students' creativity in learning according to the Minimum Completion Criteria (KKM). Thematic learning model as a learning model enters into one type of integrated learning type integreted namely learning that uses an inter-field approach, combining fields of study by linking learning based on a particular theme so as to provide meaningful experience to students. The method of this research is classroom action research. Data collection techniques used are observation, test methods, and documentation methods. The results of the study after being examined can be seen that the creativity of students from cycle to cycle has increased, which is 40% from the first cycle to 80% in the second cycle. Based on the results of these studies, the creativity of students from cycle to cycle has increased and in the second cycle the creativity of students has reached 80% of the specified target of 75%.